2020
DOI: 10.1080/02656736.2020.1782485
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of single-session radiofrequency ablation for benign thyroid nodules of different sizes: a retrospective study

Abstract: Purpose: To compare the effectiveness of radiofrequency ablation (RFA) for benign thyroid nodules (BTNs) among groups presenting with different nodule volumes. Materials and methods: This retrospective study evaluated 186 patients with BTNs who underwent ultrasound guided RFA treatment. The BTNs were categorized into small (10 ml); medium (10-30 ml); and large (>30 ml) according to the initial volume of BTNs before ablation. The RFA procedures were performed using the moving shot technique. The volume reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 36 publications
2
24
1
Order By: Relevance
“…Currently, there is no consensus on the time points of follow-up evaluation after thermal ablation. However, most of previous articles 12,14,15 reported the volume reduction ratios and improvements of symptoms at 1, 3, 6, or 12 months after the ablation treatment of thyroid nodules. Additionally, some studies [16][17][18] suggested that ultrasound examinations and the clinical symptoms could be routinely evaluated at 1, 3, 6 and 12 months after the ablation.…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…Currently, there is no consensus on the time points of follow-up evaluation after thermal ablation. However, most of previous articles 12,14,15 reported the volume reduction ratios and improvements of symptoms at 1, 3, 6, or 12 months after the ablation treatment of thyroid nodules. Additionally, some studies [16][17][18] suggested that ultrasound examinations and the clinical symptoms could be routinely evaluated at 1, 3, 6 and 12 months after the ablation.…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…The formula for the calculation of the tumor volume was V ¼ pabc/6 [22,23] (V was the volume; a was the longest diameter, and b and c were the other two diameters of the tumor). The tumor locations were recorded as left and right lobes and cephalocaudal part (upper, middle and lower) of the thyroid.…”
Section: Pre-rfa Evaluationmentioning
confidence: 99%
“…The symptom score recorded five clinical symptoms: compression, cough, difficulty swallowing, voice change, and pain. For each positive symptom, we scored one point, with symptom scores ranging from 0 to 5 [13,18].…”
Section: Follow-upmentioning
confidence: 99%
“…A thermal ablation is a treatment option for application with benign, malignant thyroid diseases and neck metastasis [10][11][12][13][14][15][16][17]; although the use of Radiofrequency ablation (RFA) on Bethesda category III/IV nodules remains controversial. Current RFA guidelines from ATA [8] and Korea [18] do not recommend RFA for the treatment of follicular neoplasm, as there is no evidence of treatment benefit.…”
Section: Introductionmentioning
confidence: 99%